SUBOREAL/BOREAL AMMONITE SUCCESSION AT THE OXFORDIAN/KIMMERIDGIAN BOUNDARY IN THE FLODIGARRY SECTION (STAFFIN BAY, ISLE OF SKYE, UK) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2004)
The Flodigarry section at Staffin Bay, Isle of Skye, has yielded numerous ammonites both of Subboreal and Boreal affinity. This has enabled close correlation of the Subboreal and Boreal ammonite zonations, and provided new palaeontological data on levels which may be considered as a potential GSSP for the Oxfordian/Kimmeridgian boundary. The traditional Oxfordian/Kimmeridgian boundary placed at the Pseudocordata/Baylei zones boundary of the Subboreal scheme corresponds precisely to the Rosenkrantzi/Bauhini zones boundary of the Boreal scheme: this level is characterized by appearance of Pictonia together with Prorasenia replacing an older assemblage of Ringsteadia-Microbiplices (Subboreal), as well as by first occurrence of small-sized Amoeboceras (Plasmatites) – mostly A. praebauhini (Boreal). A further level which may be considered as the Oxfordian/Kimmeridgian boundary is the boundary between the Bauhini Zone and Kitchini Zone of the Boreal scheme characterized by first occurrence of Amoeboceras (Amoebites) of the A. bayi group. This level corresponds to the Planula/Galar subzones boundary of the Submediterranean scheme, i.e. it lies close to the currently accepted Oxfordian/Kimmeridgian boundary in the Submediterranean Succession.